2023
DOI: 10.1371/journal.pntd.0011377
|View full text |Cite
|
Sign up to set email alerts
|

Associations of water contact frequency, duration, and activities with schistosome infection risk: A systematic review and meta-analysis

Abstract: Background Schistosomiasis is a water-borne parasitic disease which affects over 230 million people globally. The relationship between contact with open freshwater bodies and the likelihood of schistosome infection remains poorly quantified despite its importance for understanding transmission and parametrising transmission models. Methods We conducted a systematic review to estimate the average effect of water contact duration, frequency, and activities on schistosome infection likelihood. We searched Embas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Schistosome transmission is complex and driven by human behaviour, accessibility of safe water and sanitation, occupation, and ecological conditions for freshwater snails that are the intermediate host of the parasite. Exposure to schistosomes occurs during water contact with lakes, rivers, or streams through activities including swimming, bathing, or fetching drinking water [3]. During water contact, cercariae—the free-living stage of the parasite—enter a human host by burrowing through the skin.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Schistosome transmission is complex and driven by human behaviour, accessibility of safe water and sanitation, occupation, and ecological conditions for freshwater snails that are the intermediate host of the parasite. Exposure to schistosomes occurs during water contact with lakes, rivers, or streams through activities including swimming, bathing, or fetching drinking water [3]. During water contact, cercariae—the free-living stage of the parasite—enter a human host by burrowing through the skin.…”
Section: Introductionmentioning
confidence: 99%
“…Water contact has become a well-established proxy indicator for exposure due to the difficulties in directly measuring cercarial exposure. Previous studies have largely been cross-sectional and used self-reported water contact activities or constructed crude binary indicators of water contact for the purposes of predicting current infection [3]. Among 101 studies in a recent systematic review and meta-analysis by Reitzug et al, only 21.8% (22/101) collected snail abundance data to account for environmental factors relevant for translating water contact into parasite acquisition risk [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations